Strategy Guidance and Counseling Comprehensive Based Spiritual Intelligence for Student in the Digital Era - Caraka Putra Bhakti; Fuad Aminur Rahman; Muhammad Alfarizqi Nizamuddin Ghiffari (Universitas Ahmad Dahlan, 2019)
The purpose of this paper is to discuss strategy guidance and counseling comprehensive based on spiritual intelligence for students in the digital age. Guidance and counseling comprehensive is part of education, which is also a model of guidance and counseling that adheres to the principle of developmental guidance and counseling. The basic assumption of the Guidance and development counseling approach is the idea that healthy individual development will occur in the healthy interactions of individuals with their environment. In other words, the environment for individuals becomes a learning environment, because there are various intelligences that need to be considered in the process of individual development and spiritual intelligence is one aspect of individual development that needs attention. Spiritual intelligence is the highest form of intelligence that combines the two previous forms of intelligence, namely intellectual intelligence and emotional intelligence. Spiritual intelligence is considered as the highest intelligence because it is closely related to people's awareness to be able to interpret everything and is a way to be able to feel happiness. Especially in the digital era, the era illustrates that the technological revolution phase has changed the way and human behavior in scale, scope, complexity, and transformation from previous life experiences, requires that every individual must have good spiritual intelligence, so that they can face the development of the digital era this dynamic well.